Bottom‐Up Fabrication of a Sandwich‐Like Carbon/Graphene Heterostructure with Built‐In FeNC Dopants as Non‐Noble Electrocatalyst for Oxygen Reduction Reaction. Issue 3 (20th January 2020) - Lv, Xiaoxia; Xue, Xue; Gan, Xingyu; Lv, Chenhao; Sun, Xiaochen; Wang, Yun; Li, Liangjun; Wang, Hua
Abstract: High‐performance non‐noble electrocatalysts for oxygen reduction reaction (ORR) are the prerequisite for large‐scale utilization of fuel cells. Herein, a type of sandwiched‐like non‐noble electrocatalyst with highly dispersed FeNx active sites embedded in a hierarchically porous carbon/graphene heterostructure was fabricated using a bottom‐up strategy. The in situ ion substitution of Fe 3+ in a nitrogen‐containing MOF (ZIF‐8) allows the Fe‐heteroatoms to be uniformly distributed in the MOF precursor, and the assembly of Fe‐doped ZIF‐8 nano‐crystals with graphene‐oxide and in situ reduction of graphene‐oxide afford a sandwiched‐like Fe‐doped ZIF‐8/graphene heterostructure. This type of heterostructure enables simultaneous optimization of FeNx active sites, architecture and interface properties for obtaining an electron‐catalyst after a one‐step carbonization. The synergistic effect of these factors render the resulting catalysts with excellent ORR activities. The half‐wave potential of 0.88 V vs. RHE outperforms most of the none‐noble metal catalyst and is comparable with the commercial Pt/C (20 wt %) catalyst. Apart from the high activity, this catalyst exhibits excellent durability and good methanol‐tolerance. Detailed investigations demonstrate that a moderate content of Fe dopants can effectively increase the intrinsic activities, and the hybridization of graphene can enhance the reaction kinetics of ORR. The strategy proposed in this work gives an inspiration towards developing efficient noble‐metal‐free electrocatalysts for ORR. Abstract : A type of sandwiched‐like non‐noble electrocatalyst with highly dispersed FeNx active sites embedded in a hierarchically porous carbon/graphene heterostructure was fabricated using a bottom‐up strategy. The synergistic function of FeNC active sites, hierarchical structure and graphene render this catalyst with a high catalytic activity for ORR.